Temporal dynamics of mother-offspring relationships in Bigg's killer whales: opportunities for kin-directed help by post-reproductive females ... - Nielsen, Mia; Ellis, Samuel; Weiss, Michael; Towers, Jared; Doniol-Valcroze, Thomas; Franks, Daniel; Cant, Michael; Ellis, Graeme; Ford, John; Malleson, Mark; Sutton, Gary; Shaw, Tasli; et al. (Zenodo, 2023)
Age-related changes in the patterns of local relatedness (kinship dynamics) can be a significant selective force for shaping the evolution of life history and social behaviour. In humans and some species of toothed whales, average female relatedness increases with age which can select for a prolonged post-reproductive lifespan in older females due to both the costs of reproductive conflict and the benefits of late-life helping of kin. Killer whales ( Orcinus orca ) provide a valuable system for exploring social dynamics related to such costs and benefits in a mammal with an extended post-reproductive female lifespan. We use >40 years of demographic data to investigate the opportunities for helping and harming in the mammal-eating Bigg's killer whale by quantifying how mother-offspring social relationships change with offspring age. Our results suggest a high degree of male philopatry and female-biased budding dispersal in Bigg's killer whales, with some variability in the dispersal rate for both sexes. ... : RStudioFunding provided by: Natural Environment Research Council Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100000270 Award Number: NE/S010327/1Funding provided by: Natural Environment Research Council Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100000270 Award Number: NE/L002434/1 ...